2015
DOI: 10.1530/erc-14-0305
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary MRI characteristics in 297 acromegaly patients based on T2-weighted sequences

Abstract: Responses of GH-secreting adenomas to multimodal management of acromegaly vary widely between patients. Understanding the behavioral patterns of GH-secreting adenomas by identifying factors predictive of their evolution is a research priority. The aim of this study was to clarify the relationship between the T2-weighted adenoma signal on diagnostic magnetic resonance imaging (MRI) in acromegaly and clinical and biological features at diagnosis. An international, multicenter, retrospective analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 20 publications
10
87
2
3
Order By: Relevance
“…These results confirm and build upon previous studies on T2-weighted MRI signal intensity in acromegaly. As shown previously, T2-hypo-intensity is more frequent in smaller adenomas that are less invasive (Hagiwara et al 2003, Heck et al 2012, Potorac et al 2015. Also, T2-hyper-intensity is more frequent in sparsely granulated pituitary adenomas (Hagiwara et al 2003, Heck et al 2012.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These results confirm and build upon previous studies on T2-weighted MRI signal intensity in acromegaly. As shown previously, T2-hypo-intensity is more frequent in smaller adenomas that are less invasive (Hagiwara et al 2003, Heck et al 2012, Potorac et al 2015. Also, T2-hyper-intensity is more frequent in sparsely granulated pituitary adenomas (Hagiwara et al 2003, Heck et al 2012.…”
Section: Discussionsupporting
confidence: 75%
“…It has been previously shown that lower baseline GH and IGF1 levels are associated with better hormonal responses to SSA treatment, expressed in terms of IGF1 normalization and achievement of a GH threshold concentration 23:11 (Mercado et al 2007, Melmed et al 2010. Here and previously we reported that T2-hypo-intense adenomas have higher baseline GH and IGF1 levels despite having smaller and less invasive tumors than non-T2 hypointense adenomas (Potorac et al 2015). Here we show that these patients have greater percentage decreases from baseline in hormones and tumor size during primary SSA therapy.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations